ENZYMES OF PROL1NE DEGRADATION AND THEIR REGULATION IN DIFFERENT ORGANS OF $SALMO~ISCHCHAN$ (Proceedings of the YSU B: Chemical and Biological Sciences, 2004)
Activation of proline oxidaze (PO) and pirolin-5-caroxilate-dehidrogenaze (P5KD) in the organs of Salmo ischchan has been investigated. In comparison with other organs high activity of the enzymes has been found in the heart of fish. The activity of proline degradation enzymes in kidney increases 13 times during laying of hardroe of the females and in the kidney of the male – 3.5 times. Citrate stimulates the activity of PO and P5KD in all organs, except the gills and the heart. The complex of citrate and ATP in liver stimulates the activity of the mentioned enzymes over 4 times.
Keywords: proline oxidaze; pirolin-5-caroxilate-dehidrogenaze; fish organs; activity of the enzymes